The idolatry of accreditation in higher education: enhancing our understanding. Issue 2 (4th May 2022) - Romanowski, Michael H.
ABSTRACT: Worldwide accreditation systems for higher education are used by institutions and programmes to demonstrate their legitimacy to deliver quality education. Although there are many perceived benefits and criticisms of accreditation and little empirical research on its impact for improvement, there is still an increasing demand for this form of quality assurance. This essay applies the lens of idolatry to provide a distinctive perspective and offer insight into accreditation. The theory of idolisation and nine characteristics of idols provides a means to understand accreditation power over institutions, its demands, its impact on institutions and professors and its ability to shape and legitimise a particular understanding of education and academic disciplines.